Measurement of Dynamic Urethral Pressures with a High Resolution Manometry System in Continent and Incontinent Women - Kirby, Anna C (Female Pelvic Med Reconstr Surg, 2015)
OBJECTIVES: Female stress urinary incontinence (SUI) is caused by urethral dysfunction during dynamic conditions, but current technology has limitations in measuring urethral pressures under dynamic conditions. An 8-French high resolution manometry catheter (HRM) currently in clinical use in gastroenterology may accurately measure urethral pressures under dynamic conditions because it has a 25ms response rate and circumferential pressure sensors along the length of the catheter (ManoScan® ESO, Given Imaging). We evaluated the concordance, repeatability, and tolerability of this catheter. METHODS: We measured resting, cough, and strain maximum urethral closure pressures (MUCPs) using HRM and measured resting MUCPs with water perfusion side-hole catheter urethral pressure profilometry (UPP) in 37 continent and 28 stress incontinent subjects. Maneuvers were repeated after moving the HRM catheter along the urethral length to evaluate whether results depend on catheter positioning. Visual analog pain scores evaluated the comfort of HRM compared to UPP. RESULTS: The correlation coefficient for resting MUCPs measured by HRM vs. UPP was high (r = 0.79, p<0.001). Repeatability after catheter repositioning was high for rest, cough, and strain with HRM: r= 0.92, 0.89, and 0.89. Mean MUCPs (rest, cough, strain) were higher in continent than incontinent subjects (all p < 0.001) and decreased more in incontinent subjects than continent subjects during cough and strain maneuvers compared to rest. CONCLUSIONS: This preliminary study shows that HRM is concordant with standard technology, repeatable, and well tolerated in the urethra. Incontinent women have more impairment of their urethral closure pressures during cough and strain than continent women.